The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/jpo.0b013e318195c140
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation for Those With Transtibial Osteomyoplastic Amputation

Abstract: Often encountered in traditional transtibial amputation is a condition that constitutes pain, swelling, sense of instability, bone and soft tissue atrophy, and prosthetic difficulties, resulting in decreased function. One innovative method for maximizing the rehabilitation capability after amputation surgical reconstruction is osteomyoplastic transtibial amputation, commonly called the "Ertl procedure" (Ertl and Ertl, Prosthetics and Patient Management: A Comprehensive Clinical Approach. 2006). A standard for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
1
8
0
Order By: Relevance
“…Two studies reported evidence in favor of the bone bridge compared to the non–bone bridge TTA, in the topics of Subjective analysis and Function (patient-reported functional outcomes). 12,16 A favorable outcome is consistent with a large body of articles, 5,2027 not considered in this review due to the screening process; primarily because they were level IV and V case studies or reports. These reports add to the reported benefits of the bone bridge technique compared to the non–bone bridge technique.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Two studies reported evidence in favor of the bone bridge compared to the non–bone bridge TTA, in the topics of Subjective analysis and Function (patient-reported functional outcomes). 12,16 A favorable outcome is consistent with a large body of articles, 5,2027 not considered in this review due to the screening process; primarily because they were level IV and V case studies or reports. These reports add to the reported benefits of the bone bridge technique compared to the non–bone bridge technique.…”
Section: Discussionsupporting
confidence: 68%
“…An alternative addition to transtibial amputation is a bone bridge, which considers limitations of traditional procedures. 5 A bone bridge technique described by Ertl 6 reportedly restores intraosseous pressure through canal obliteration while expanding the area of terminal support by creating a bony bridge between the distal tibia and fibula. 6 The stabilization of the tibia and fibula through this bone bridge eliminates potentially painful movement of the fibula while creating a blunt surface at the distal end of the RL.…”
Section: Introductionmentioning
confidence: 99%
“…11 This technique has been suggested to improve the overall physiology of the residual limb by maintaining the medullary canal pressures and improving vascularization of the remaining tissues. 12,13 Unlike a non-Ertl amputation, the Ertl creates a “bone bridge” to connect the tibia and fibula, seals the medullary canal, and sutures the anterior and posterior residual musculatures together. 12 The Ertl has been suggested to tolerate greater direct load bearing of the distal end of the residual limb (standing directly on the stump without a prosthetic socket) than the non-Ertl procedure.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Unlike a non-Ertl amputation, the Ertl creates a “bone bridge” to connect the tibia and fibula, seals the medullary canal, and sutures the anterior and posterior residual musculatures together. 12 The Ertl has been suggested to tolerate greater direct load bearing of the distal end of the residual limb (standing directly on the stump without a prosthetic socket) than the non-Ertl procedure. 12,14 Greater residual limb load bearing has the potential to positively impact long-term outcomes by increasing symmetrical loading between limbs, thereby reducing the increased risk of osteoarthritis in joint proximal to the site of amputation and the intact limb joints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation